The Silver Economy in the context of Corporate Social Responsibility - Szewczyk, Monika (Annales. Etyka w Życiu Gospodarczym, 2019)
Corporate social responsibility is a concept responding to climate change, environmental problems and the needs of stakeholders. Business makes an effort to act in the changing conditions, thus adapting to the expectations of the stakeholders and following the principles of sustainable economic development and social responsibility. One of the changes taking place in the current economic and social world is the change in the demographic structure of the population. The subject of the ageing population is often discussed, usually as a negative aspect in the context of changes in the pension system, health care costs or the employment conditions of older people. The principles of corporate social responsibility, such as social inclusion, anti-discrimination, and facilitating access to products and services create the basis for the development of the economy, focused on the use of the purchasing potential of older people. Thus, the perception of the demographic changes in this context becomes the ground for the formation of perspective solutions and the development of the silver economy. This model of the economy can be understood as a system which is based on adapting the production and distribution of products and services to older people. The main aim of this article is to present the challenges for companies in terms of the problems connected with an ageing population, as well as to present the main features of the concept of the silver economy in the context of corporate social responsibility. Moreover, considering the development of the silver economy, characteristics of older people as consumers should be taken into account. In this context, there are many stereotypes associated with the activities of the elderly. The article also notes the profile of potential customers of the silver economy, with a particular emphasis on the approach of the elderly to innovation, tradition and a broadly understood sense of security.